The Viability of the Mult-Door Courthouse Having Criminal Jurisdiction: A Critical Analysis (British Journal of Multidisciplinary and Advanced Studies, 2025)
The Modern Alternative Dispute Resolution was introduced into the world, as a form of method that would aid in alleviating the hardships and disadvantages of courtroom litigation, However, upon careful scrutiny of the systems that employ this method of dispute resolution; it comes to ones’ focus that the institutions are one-sided in the types of cases they entertain. Cases in point, which this write-up will center on, are the Lagos MultiDoor courthouse. These are one of the current institutions through which Alternative Dispute Resolution mechanisms are being practiced. However, a major drawback characterized by these alternative courts is that their jurisdictions are limited to resolving civil cases. In essence, the other most important aspect of the legal system is neglected, which is the criminal justice system i.e criminal cases. Criminal cases are out rightly excluded from reaping the benefits of this valuable and beneficial concept.A further research by this write-up brings into limelight certain processes within the criminal justice system which are similar to the ADR processes themselves. This article aims at highlighting these criminal law methods which will aid in resolving criminal disputes amicably and agreeably, just like the ADR processes. The mechanisms in focus will be plea bargaining, restorative justice and compoundable offences. The similarities between these methods and these of the ADR processes. The write-up will then look into how these criminal law processes can be incorporated and employed into the multi-Door courthouses. In order that the MDCs will have concurrent jurisdictions of both civil and criminal cases.